Program Pendampingan Pemanfaatan Media Augmented Reality Berbasis Audio bagi Siswa Tuna Daksa dalam Pembelajaran Hafalan Al Qur’an di SLB A ’Aisyiyah Ponorogo - Nurul Azizah; Haziq Farda Isyrafi; Defi Firmansah; Muhammad Khadafi Nusantara; Rafki Fauzan; Andi Muhammad Zuljalal (Abdimas Indonesian Journal, 2026)
This research aims to develop Augmented Reality (AR)-based inclusive learning media to help students with disabilities memorize the Qur'an and support more inclusive and effective learning. The mentoring program is carried out through the stages of identifying partner needs through observation and interviews, designing Audio Control-based AR media, implementation through modules and socialization to teachers and parents, and direct implementation in the classroom. Monitoring and evaluation are carried out periodically using pre-test and post-test. The results of the program show that Audio Control-based AR media helps improve Qur'an memorization through sound features, audio repetition, and interactive displays that support independence and focus on learning. From 9 students, the number of students with good memorization increased from 1 to 5 students, accompanied by an increase in reading skills, independence, concentration, and learning motivation. Teacher and parent assistance also strengthens learning outcomes. Overall, Audio Control-based AR media has proven to be effective as an inclusive learning strategy for students with disabilities. However, learning still requires an adaptive approach through the collaboration of teachers and parents. Further research suggests developing advanced features, involving larger subjects, as well as expanding the scope to different types of special needs.